Review of the genus Promalactis (Lepidoptera: Oecophoridae) Meyrick, 1908 (II). The suzukiella group, with descriptions of eight new species - Wang, Shuxia; Jia, Yanyan (Zootaxa, 2017)
Fifty-five species of the genus Promalactis Meyrick, 1908 are placed in the suzukiella group based on the forewing patterns. Among them, eight species are described as new: P. foliprocessa Wang, sp. nov., P. similiclavata Wang, sp. nov., P. aliformis Wang, sp. nov., P. dorsiseparata Wang, sp. nov., P. albitriangula Wang, sp. nov., P. sichuanensis Wang, sp. nov., P. huemeri Wang, sp. nov., and P. grandacantha Wang, sp. nov.; the females of P. subclavata Du, Wang et Li, 2014 and P. undulata Wang, Du et Li, 2013 are described for the first time. Photographs of adults and genitalia of the new species are provided; a map showing the type localities of the 55 species in the suzukiella group is given. Species belonging to the suzukiella group are listed.